Real estate markets and bank distress - Michael Koetter; Tigran Poghosyan (Deutsche Bundesbank, 2008)
We investigate the relationship between real estate markets and bank distress among German universal and specialized mortgage banks between 1995 and 2004. Higher house prices increase the value of collateral, which reduces the probability of bank distress (PDs). But higher prices at given rents may also indicate excessive expectations regarding the present value of real estate assets, which can increase PDs. Increasing price-to-rent ratios are positively related to PDs and larger real estate exposures amplify this effect. Rising real estate price levels alone reduce bank PDs, but only for banks with large real estate market exposure. This suggests a positive, but relatively small 'collateral' effect for banks with more expertise in specialized mortgage lending. Likewise, lower price-to-rent ratios are estimated to reduce the riskiness of banks. The multilevel logit model used here further shows that real estate markets are regionally segmented and location-specific effects contribute significantly to predicted bank PDs.
Keywords: G21; C25; G3; 330; Real estate; distress; universal vs. specialized banks; Immobilienmarkt; Bankrisiko; Immobilienpreis; Kreditrisiko; Universalbank; Hypothekenbank; Vergleich; Deutschland; Deutschland